Adjusted Individual Educational Report Sebagai Media Konstruksi Komunikasi Pihak Sekolah dan Stakeholders - Misnan Misnan (KOMUNIKATA57, 2020)
The problem is the construction of social reality in formulating AIEP (Adjusted Individual Educational Program) and making AIEP as a more objective, adaptive and realistic representation of coordination as a communication media for schools, parents and stakeholders. The method is descriptive qualitative. The result showed that the application of the concept of AEIP is very useful because it can accommodate various needs of students. It is no longer appropriate to apply the same assessment tools to all students because they have different abilities and needs. On the other hand, there is urgency to the case of students with special needs who choose to study in public schools. These students need their own assessment tools because they have unique abilities and are not owned by the average normal student. One of the tools to assess students with special needs is to create an IEP program. Through IEP, teachers and other team members can create a special curriculum for these students, but still based on the school curriculum in general.